The role of working memory in contextual cueing of visual attention. (September 2022) - Vicente-Conesa, Francisco; Giménez-Fernández, Tamara; Shanks, David R.; Vadillo, Miguel A.
Abstract: It is usually easier to find objects in familiar contexts that we have seen before. The type of learning that underlies this facilitation, known as contextual cueing, has been understood as an incidental and automatic process given that, among other reasons, it seems to be independent of working memory (WM) resources. This claim has found support in previous research showing that contextual cueing can be acquired latently, while participants perform a demanding WM task. However, previous studies have not always found this pattern of results and, in general, the available evidence is far from conclusive. The aim of the present study was to clarify the role of WM in contextual learning with two large-sample, confirmatory experiments. Our results show a robust contextual cueing effect even when visuospatial working memory resources were recruited by a demanding secondary task.